Baicalin Mitigates Cardiac Hypertrophy and Fibrosis by Inhibiting the p85a Subunit of PI3K - Lu He; Min Zhu; Rui Yin; Liangli Dai; Juan Chen; Jie Zhou (Biomedicines)
Background: Heart failure (HF) is a serious public health concern. Baicalin is one of the major active ingredients of a traditional Chinese herbal medicine, Huang Qin, which is used to treat patients with chest pain or cardiac discomfort. However, the underlying mechanism(s) of the cardioprotective effect of baicalin are still not fully understood. Methods: Isoprenaline injection or transverse aortic constriction-induced animal models and isoprenaline or angiotensin 2 administration-induced cell models of heart failure were established. Baicalin (15 mg/kg/day or 25 mg/kg/day) was administered in vivo, and 10 μM baicalin was administered in vitro. Potential pharmacological targets of baicalin and genes related to heart failure were identified via different databases, which suggested that PI3K–Akt may be involved in the effects of baicalin. Molecular docking was carried out to reveal the effect of baicalin on p85a. Results: We observed significant antihypertrophic and antifibrotic effects of baicalin both in vivo and in vitro. The mean cross-sectional area of cardiomyocytes recovered from 390 μm2 in the HF group to 195 μm2 in the baicalin-treated group. The area of fibrosis was reduced from 2.8-fold in the HF group to 1.62-fold in the baicalin-treated group. Baicalin displayed a significant cardioprotective effect via the inhibition of the PI3K signaling pathway by binding with five amino acid residues of the p85a regulatory subunit of PI3K. The combination treatment of baicalin and an inhibitor of PI3K p110 demonstrated a stronger cardioprotective effect. The mean ejection fraction increased from 54% in the baicalin-treated group to 67% in the combination treatment group. Conclusions: Our work identified baicalin as a new active herbal ingredient that is able to treat isoprenaline-induced heart dysfunction and suggests that p85a is a pharmacological target. These findings reveal the significant potential of baicalin combined with an inhibitor of PI3K p110 for the treatment of heart failure and support more clinical trials in the future.